Mobile application for live streaming - communication and control - Chua, Sean Wei Jie (2017)
Communication is the process whereby information is being sent and received among individuals, and it is an integral aspect of human beings’ lives. In the past, non-verbal communication has always been done through text written on papers and passed physically from one individual to another. With the advent of technology within the last two decades, there has been a change in tide. Communication is now mostly done online and explains why usages of social media platforms like WhatsApp, Facebook and Instagram, just to name a few, have become so prolific over the recent years. Other than maintaining relationship, online communication has also propelled the human race forward much faster than before through the instantaneous sharing of knowledge and abilities. While experimenting with communications between mobile applications through the building of different applications, the author wanted to further a greater cause of benefitting education and built the mobile applications with this cause in mind. The author hopes that these mobile applications will eventually empower education by encouraging communications and discussion-based learning. The mobile applications are developed using the latest native iOS development tool Xcode, using the language Swift 4 that was only recently released in September 2017. Swift 4 is a native programming language developed solely by Apple to replace its predecessor, Objective-C. Despite the instability, the new language since its inception have progressed leaps and bounds within a short span of time. With the increasing trend of live streaming, the author also conducted literature reviews on prevalent live streaming mobile with the intention of utilising the beneficial aspect of this functionality to improve ELIVE’s capabilities as an educational platform. The author also took the liberty to conduct detailed studies on students to find out how social media helps to promote communication and how it could be integrated into the future of the mobile application, ELIVE so that students could better communicate with each other and learn using the app.